New Islamic equity style indices and their application in Malaysian capital markets / Shahrin Saaid Shaharuddin - Shahrin Saaid , Shaharuddin (2017)
An equity style index is a form of stock market index which has been developed as a benchmark to measure the performance of stocks by grouping stocks according to categories and characteristics. In the case of Malaysia, an Islamic equity style index which measures the performance of Islamic stocks has yet to be developed. This study will therefore attempt to address this issue by constructing new Islamic equity style indices which will then be tested for its benefits and potential utility by performing tests based on its information transmission efficacy and against the Fama and French threefactor model. Firstly, this dissertation will examine the importance of developing Islamic equity style indices by surveying relevant literature and reviewing the Islamic stock market in Malaysia and abroad. Secondly, the new Islamic equity style indices in this study will be created based on style classification systems as proposed by the Russell Co. and Focardi et al. (2004) as well as methodologies provided for through contemporary methods. Thirdly, the newly constructed Islamic equity style indices will be tested for its efficacy in information transmission by using the Vector Autoregression (VAR) model. Finally, this study will then attempt to analyse the Fama and French (1992, 1993) threefactor model by proving the validity of the model using the newly developed Fama and French factors. The results of the VAR test indicates that the LV and LG indices have short-run dynamics and precedes macroeconomic variables and is useful for purposes of predicting future economic conditions. The evidence also suggests that Islamic equity style indices follow the Fama and French three-factor model despite the persistence of the reversal of size effect. These findings are useful for investors, researchers and policy makers for purposes of portfolio construction, benchmarking and forecasting.